Design of Urban Indicators to Optimize the Implementation of Low-Impact Techniques in Semi-Arid Cities - Valeria Volpi-León; Juan Carlos Seck-Tuoh-Mora; Carlos Alfredo Bigurra-Alzati; Alma Delia Juárez-Sedano; Liliana Lizárraga-Mendiola (Applied Sciences)
The study area is a densely populated residential zone located in central Mexico, characterized by a semi-arid climate and diverse land uses, including domestic, commercial, and services. In the study area, water demand is assessed based on land use requirements set by national and local regulations, and an urban configuration pinpoints spaces suitable for rainwater harvesting for self-consumption. This research proposes indicators based on urban, demographic, and hydrological parameters to assess the effectiveness of low-impact development (LID) techniques, such as rooftop rainwater harvesting, aimed at reducing water scarcity in a residential area vulnerable to water shortages in a semi-arid city in the Global South. Additionally, hydrological design conditions are defined to estimate the potential volumes of recoverable water. Indicators for infiltrated water, available water for consumption, runoff water, and sufficient water are established. This framework enables the development of strategies to mitigate water scarcity and improve water management in the area.